Teachers as Researchers: Skills and Challenges in Action Research Making (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
The study aims to determine the level of competency of teachers as researchers as well as determine the factors that affect them in action research. Quantitative research, specifically the descriptive design, was used. It was conducted in the second congressional district of Quezon Province, Philippines, composed of 147 elementary and secondary teachers who have started writing action research. Relevant data were gathered through a validated survey questionnaire. The study was facilitated with confidentiality. Responses were treated through weighted arithmetic mean. The results revealed that 1) 32 out of 38 skills in action research writing landed in the lower bracket of the competent level. However, six skills landed on the less competent level. It has been noted that teacher-researchers are weak in choosing the tools for data analysis and interpretation, encoding quantitative and qualitative data, and interpreting results from the software. They were also less competent in publishing their completed action research. 2) Knowledge, attitude, and resources were the factors that affected teachers in their engagement in conducting action research. The respondents were limited to 147 retrieved questionnaires from the districts of Dolores, San Antonio, Candelaria, Sariaya, and Lucena. For further study, it was suggested that future researchers might come up with a larger scope and population. The findings of the research may be important to teachers and administrators since it will serve as a baseline for the status of action research-making in the district. The results should be the focus of capability-building activities of teachers.